Impact of Interactive Multimedia-based Nutrition Education Programme (IMNEP) on nutrition KAP and anthropometric parameters among overweight and obese primary school children in Kota Bharu - Dali, Wan Putri Elena Wan (2018)
Childhood obesity has been a major public health concern in Malaysia and other developed countries for years. Focus of the present study was to evaluate the effectiveness of developed intervention known as Interactive Multimedia-based Nutrition Education Package (IMNEP) targeting on overweight and obese children in Kota Bharu, Kelantan. This study had two phases; development of the IMNEP and impact of the IMNEP. Phase I describes how the IMNEP developed and its contents. The IMNEP were then evaluated among school children (n=50), review panels (n=10) and parents (n=8). In Phase II, 4-arm cluster randomized school-based trial was conducted among primary schools in Kota Bharu. Fourteen participated schools were randomly assigned into one of four groups: three intervention groups (CPI: children, parents intervention; COI: children only intervention and POI: parents only intervention) or a control group (COC: children only control). Intervention groups were exposed to animated explanatory videos, an education video game entitled My Healthy Eating and active gaming exercises by using XBOX 360 over a 12-week and another 12-week without intervention. In Phase I, majority of the respondents gave positive responses and they felt that this IMNEP was interesting and engaging in terms of variety topics included, graphics, contents, animations and purposes as new medium in teaching nutrition for children and parents. Some modifications has been made and come out with the final version of the IMNEP. Of the 139 respondents recruited at baseline during Phase II, 121 (87.1%) of respondents completed the 12-week of IMNEP and 112 (80.6%) completed overall 24-week of intervention study. Initially, the percentage of obesity (83.5%) was higher than those overweight (16.5%). However, after 12 weeks, the results showed reduction in the percentage of overweight and obese, significant reduction in body weight (CPI), body mass index (BMI) (CPI, POI), fat mass (POI), waist (POI) and hip (COI, POI) circumferences among those in the intervention groups. Significant increments of nutrition knowledge (CPI, POI) and practice (CPI), vitamin A intake (CPI, COI) as well as higher number of those physically active especially based on described best activities (COI) and Total PAQ-C score (POI) were also shown among intervention groups. By using RMANOVA test, the respondents in intervention groups keep experiencing significant increments of nutrition knowledge (COI, POI), vitamin A intake (CPI, COI) and continued to be physically active (COI, POI) seen in Total PAQ-C from baseline to week 24. Eating habits for milks, fruits and vegetables groups remain unchanged. In this cohort, the IMNEP was found to be beneficial in effectively increased nutrition knowledge and physical activity outcomes but not in selected food groups and nutrient intakes outcomes. Positive results in anthropometric measurements were also achieved in intervention groups. Targeting both parents and children in childhood obesity prevention interventions are crucial because parents’ involvement has powerful effects on a child’s perception and behaviours towards food and physical activity.